Disability Incidence Rates for Men and Women in 23 Countries: Evidence on Health Effects of Gender Inequality. (20th November 2020) - Lee, Jinkook; Meijer, Erik; Phillips, Drystan; Hu, Peifeng
Abstract: Background: Inequality in gender varies across social contexts, which may influence the health of both men and women. Based on theories of gender as a social system, we examine whether systematic gender inequality at the macro-level influences health of men and women. Method: Using harmonized panel data from the Gateway to Global Aging Data in 23 high- and middle-income countries ( N = 168 873), we estimate disability prevalence and incidence for men and women ages 55–89 (2000–2016). Within each country or geographic region, we also investigate gender differences in age gradients of the probability of disability onset. We, then, pool data from all countries and test the hypothesis that gender inequality increases the probability of disability onset. Results: We found substantial cross-country variation in disability incidence rates, and this variation is greater for women than for men. Among ages 65–69, disability incidence rates ranged from 0.4 to 5.0 for men and from 0.5 to 9.4 for women. Our within-country analysis showed significant gender differences in age gradients of the probability of disability onset in the United States, Korea, Southern Europe, Mexico, and China, but not in Northern, Central, and Eastern Europe, England, and Israel. Testing hypothesized effects of gender inequality, we find that gender inequality is significantly associated with the probability of disability onset for women, but not for men. Conclusions: Macro-level societal gender inequality is significantly associated with the probability of disability onset for women. Reducing and eliminating gender inequality is crucial to achieving good health for women.